Formação docente como profissional da aprendizagem em programas de pós-graduação stricto sensu em administração: perspectivas à inovação educacional - Begnini, Karine Cecilia Finatto (2023)
The essence of the university is the integral human formation and the professor is the transforming agent, therefore, the graduate has a fundamental role in the formation of this professional, considering the perspective of educational innovation. Pedagogical and educational training for learning in the exercise of university teaching is inserted in training spaces in transformation. The training spaces and strategies in postgraduation prioritize teacher training for research, thus raising the problem of the need for qualification for the learning processes. The concerns of the academic debate in relation to the quality of students' education in the face of social transformations, considering the profiles of professional training, refer to paradigmatic changes, which imply educational innovations in stricto sensu Graduate Programs in Business Administration. The general objective of the research is to understand how the pedagogical and educational formation for the exercise of teaching in the functions of conducting learning processes, in Graduate Programs in Administration stricto sensu, is present in the legislation and how it is debated in research published in journals in the period 1996-2021, aiming at educational innovation. In order to explain the theoretical dimension of pedagogical training for teaching in Business Administration, the educational and pedagogical training for exercising the functions of conducting the learning process in Graduate Programs is discussed. To this end, understandings about the professional training of university professors and innovation in teaching training are developed (AUDY, 2017; CUNHA, 2013, 2019; DELORS et al, 1998; MASETTO, 2003, 2011, 2015; MASETTO; GAETA, 2019; PERRENOUD, 1999; PIMENTA; ANASTASIOU, 2002; ROGERS, 2000; ZABALA, 2015; ZABALZA, 2003). This is a theoretical investigation, with a qualitative and exploratory approach, based on documentary research, Systematic Literature Review (SLR) and literature, referring to the process of teacher training in Postgraduate Programs in Business Administration in Brazil. Given the importance of understanding the concept of teacher training, the data are systematized and interpreted through content analysis (BARDIN, 2011). Research on the pedagogical and educational training of teachers who work in training administrators is scarce and indicates the need to continue research. In exploring the articles arising from RSL, the concepts of teacher training, criticism and proposals and perspectives for innovation were explored. The analysis indicated that in the area of Administration, studies do not address professional competence in conducting learning processes. Despite appearing in the evaluation forms of the Coordination for the Improvement of Higher Education Personnel (CAPES) the question of teaching in this area, effectively, it still remains linked to scientific production, disregarding the other training dimensions indicated by Delors et al. (1998), Masetto (2003, 2013), Zabala (2015) and Rogers (2000). This research conceives suggestions aimed at educational innovation, based on subjects, objects and contexts (MENEGHETTI, 2013), seeking to subsidize actions that provide opportunities for the necessary transformations in the training of university professors within the scope of stricto sensu Graduate Programs in Business Administration. It is intended to contribute to these discussions, highlighting the pertinence of this debate in view of the need for educational innovation.